Age and Racial/Ethnic Differences in Dietary Sources of Protein, NHANES, 2011–2016 - Beasley, Jeannette M.; Firestone, Melanie J.; Popp, Collin J.; Russo, Rienna; Yi, Stella S. (Frontiers in Nutrition, 2020)
Background: Dietary protein serves a pivotal role in providing the body with essential amino acids, which are required for the maintenance of body proteins, and the assimilation of structural and functional components required for basic survival. Understanding dietary protein sources can help inform intervention efforts to increase protein intake that will accommodate the diversity of the United States. Objective: The purpose of this analysis was to identify the top 10 food category sources of dietary protein by age and race and ethnicity in a nationally representative sample. Methods: Cross-sectional data on adults (18+ years) from the National Health and Nutrition Examination Survey (NHANES) 2011-2016 with one 24-hour dietary recall were analyzed (n=15,697). Population proportions were calculated based on protein intake (g/day) for What We Eat In America food categories. Results: The analytic sample (n=15,697) was 15.0% Hispanic (95%CI [12.1, 17.9], 65.0% non-Hispanic White (95%CI [60.8, 69.3]), 11.5% non-Hispanic Black (95%CI [9.1, 13.9]), 5.4% non-Hispanic Asian (95%CI [4.3, 6.6]) and 3.1% other (95%CI [2.5, 3.6]). In all racial and ethnic groups, chicken (whole pieces) was the top-ranked source of dietary protein. In addition to chicken (whole pieces), beef (excludes ground), eggs and omelets, and meat mixed dishes food categories ranked in the top ten sources of protein for every race/ethnicity. Only two solely plant-based proteins appeared in the top ten sources: beans, peas and legumes for Hispanics, and nuts and seeds for Other. Conclusion: The top ten sources of protein accounted for over 40% of dietary protein irrespective of race/ethnicity or age category, having major implications for the sustainability of our nation’s food supply. Public health strategies that encourage diversity in protein sources in food preparation and incorporate legumes and nuts along with poultry have the potential to shift the overall population protein intake distribution towards improving overall diet quality.